Relative distribution of subcutaneous fat in childhood - Hajniš, Karel (Array, 1990)
This study deals with changes in the relative distribution of subcutaneous fat in 10,661 Czech and Slovak children aged 1-1/2 to 15 years. Beginning with the seventh year of age, it is seen that a centripetal trend of displacement of subcutaneous fat from limbs, head, and neck to the trunk takes place